2010
DOI: 10.1007/s00018-010-0524-2
|View full text |Cite
|
Sign up to set email alerts
|

Plant ribosome-inactivating proteins type II induce the unfolded protein response in human cancer cells

Abstract: Cytotoxic ribosome-inactivating proteins (RIPs) of type II such as ricin were investigated as anti-cancer agents, but also pose a threat as biological weapons. The molecular mechanism leading to their toxic effects is, however, not yet clear. The current paradigm, which states that the irreversible depurination of 28S rRNA results in a general translational arrest eventually leading to cell death, has been questioned. Using micro-array, qRT-PCR and Western blot, we identified the unfolded protein response (UPR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 32 publications
2
45
1
Order By: Relevance
“…For aBSM, a molecular mass of 400 kDa was assumed (25,26). 920 GalNAc residues/molecule were estimated for aBSM based on data available for porcine submaxillary mucin, which possesses a molecular mass of 10 6 Da with ϳ2300 GalNAc residues/molecule (20).…”
Section: Binding Analysis Of Riproximin In a Carbohydratementioning
confidence: 99%
See 1 more Smart Citation
“…For aBSM, a molecular mass of 400 kDa was assumed (25,26). 920 GalNAc residues/molecule were estimated for aBSM based on data available for porcine submaxillary mucin, which possesses a molecular mass of 10 6 Da with ϳ2300 GalNAc residues/molecule (20).…”
Section: Binding Analysis Of Riproximin In a Carbohydratementioning
confidence: 99%
“…Within the cell, the A-chain, an rRNA N-glycosidase, depurinates the 28S RNA, leading to transcriptional arrest and eventually cell death (5). Recently, it was shown that the mode of action also involves the induction of the unfolded protein response (6).…”
mentioning
confidence: 99%
“…5 The high toxicity after internalization of these RIPs is related to cell death resulting from apoptosis induction. [6][7][8] Pancreatic ductal adenocarcinoma (PDAC) has one of the worst survival rates of all malignancies. Despite continued efforts over the past decades to improve diagnosis and treatment, the prognosis of patients with PDAC is still poor, and incidence rates are virtually identical to mortality rates.…”
Section: Introductionmentioning
confidence: 99%
“…The differential sensitivity to Rpx observed in our panel of cell lines caused us to relate the expression profile of these cells with their sensitivity to Rpx. The lectin's potential to induce apoptosis 8 was then basis to monitor the expression of apoptosis related genes in PDAC cells following Rpx treatment. The modulation of gene expression observed in this experiment prompted the choice of TRAIL as combination partner of Rpx, and this combination showed synergistic antiproliferative activity.…”
Section: Introductionmentioning
confidence: 99%
“…Horrix et al (2011) Bhaskar et al (2012) have examined both dose and time-dependent transcriptional responses induced by abrin in the adult mouse brain. Swiss albino mice (two experimental groups of 6 animals each) were exposed to 1 (2.83 μg/kg) and 2 LD 50 dose of abrin (5.66 μg/kg body weight) by intra-peritoneal route.…”
mentioning
confidence: 99%